Fixation of Light Weight Polypropylene Mesh with n-Butyl-2-cyanocrylate in Pelvic Floor Surgery: Experimental Design Approach in Sheep for Effectiveness Evaluation. (28th June 2015) - Barbosa, Sandra; Nieves, Tania; García, Félix; Cepeda, Eva; Moll, Xavier; Marco, Alberto; Weis, Christine; Turon, Pau; Vergara, Patri
Abstract : Objective . The aim of this study was to find a proper experimental design and to evaluate n-butyl-2-cyanoacrylate (Histoacryl) as a fixation method for a light-weight and large pore PP mesh ( Synthetic PP Mesh-1 ) using the sheep as an animal model. Methods . Posterior vaginal implantation by means of episiotomy was used to implant 8 ewes which were evaluated macroscopically and histologically at 3 months (n = 4 ) and 6 months (n = 4 ) post-surgery. In previous pilot studies anterior vaginal implantation was evaluated, as well as different synthetic mesh materials, sizes and fixation methods (n = 1 to 3) during three weeks. In all cases a clinical evaluation of the animal was performed. Results . A reduction in the mesh size ( Synthetic PP Mesh-1 ) together with precise application of the surgical glue Histoacryl to fix the mesh yielded significantly better histocompatibility results (P < 0.01 ) compared to larger size or other fixation methods. Conclusion . The combination of Synthetic PP Mesh-1 with Histoacryl offered a high degree of graft integration without vaginal ulceration and a minimal foreign body reaction, being the sheep a proper animal model to test these types of medical devices.